The ACTCellerate initiative: large-scale combinatorial cloning of novel human embryonic stem cell derivatives. (May 2008) - West, Michael D; Sargent, R Geoffrey; Long, Jeff; Brown, Colleen; Chu, Jing Song; Kessler, Steven; Derugin, Nikita; Sampathkumar, Janani; Burrows, Courtney; Vaziri, Homayoun; Williams, Roy; Chapman, Karen B; et al.
Human embryonic stem cells offer a scalable and renewable source of all somatic cell types. Human embryonic progenitor (hEP) cells are partially differentiated endodermal, mesodermal and ectodermal cell types that have not undergone terminal differentiation and express an embryonic pattern of gene expression. Here, we describe a large-scale and reproducible method of isolating a diverse library of clonally purified hEP cell lines, many of which are capable of extended propagation in vitro . Initial microarray and non-negative matrix factorization gene-expression profiling suggests that the library consists of at least 140 distinct clones and contains many previously uncharacterized cell types derived from all germ layers that display diverse embryo- and site-specific homeobox gene expression. Despite the expression of many oncofetal genes, none of the hEP cell lines tested led to tumor formation when transplanted into immunocompromised mice. All hEP lines studied appear to have a finite replicative lifespan but have longer telomeres than most fetal- or adult-derived cells, thereby facilitating their use in the manufacture of purified lineages for research and human therapy.